2013
DOI: 10.4318/tjg.2013.0696
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of BioEnterics intragastric balloon in obese patients

Abstract: Girifl ve Amaç: Bioenterik intragastrik balonun kilo kayb› için etkili ve invazif olmayan bir metod oldu¤u düflünülmektedir. Bu metodun kilo kayb› üzerindeki uzun süreli etkisini de¤erlendirmeyi amaçlad›k. Gereç ve Yöntem: 2009 Haziran ay›ndan 2011 Haziran ay›na kadar 32 hastaya (14 erkek, 18 kad›n)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Endoscopic insertion of the intragastric balloon (IGB) is a minimally invasive procedure leading to premature satiation, prolonged satiety, and influences the hormone levels regulating energy balance [1][2][3][4][5][6][7] The weight reductions induced by IGB are retained by a relatively low number of patients over longer periods after its removal [1,[8][9][10]. As physical activity (PA) plays an important role in promoting long-term weight maintenance [11], we have evaluated changes in PA accompanying IGB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic insertion of the intragastric balloon (IGB) is a minimally invasive procedure leading to premature satiation, prolonged satiety, and influences the hormone levels regulating energy balance [1][2][3][4][5][6][7] The weight reductions induced by IGB are retained by a relatively low number of patients over longer periods after its removal [1,[8][9][10]. As physical activity (PA) plays an important role in promoting long-term weight maintenance [11], we have evaluated changes in PA accompanying IGB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its long-term effects are more questionable, with a high rate of weight regain over 2 years after treatment, though some physiologic parameters demonstrated longer-term improvement despite partial weight gain [27]. Nonetheless, some studies report a relatively high rate of maintaining weight .1 year [28]. However, our data demonstrated that increase in RMR/ mass is associated with more weight, BMI, and EW loss, whereas a decrease in RMR/mass with less decrease in these parameters, consistent with de Cleva et al [29], who described such relationship after bariatric surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Інтенсивна зміна способу життя пов'язана з незначною втратою ваги, що зазвичай не перевищує 5%. Фармакологічне лікування дозволяє додатково збільшити втрату ваги від 3 до 9% порівняно із самою лише зміною стилю життя, проте нерідко пов'язане з несприятливими побічними ефектами і не забезпечує довготривалої дії [20,36] [21,24].…”
unclassified